Genetic Anomalies of the Respiratory Tract - Cuppari, Caterina; Cutrupi, Maria C.; Salpietro, Annamaria; Sallemi, Alessia; Fusco, Monica; Parisi, Giuseppe Fabio; Salpietro, Carmelo (Current Respiratory Medicine Reviews, 2019)
Hereditary lung diseases can affect the airways, parenchyma and vasculature of the lung. Such diseases comprehend simple monogenic disorders such as Kartagener syndrome and α1-antitrypsin deficiency, in which mutations of critical genes are sufficient to induce well128;defined disease phenotypes. A major comprehension of the genetic basis of pulmonary diseases has produced new investigations into their underlying pathophysiology and contributed sometimes to clarify on more frequent sporadic forms. The presence of these structural abnormalities of the respiratory tract can be fatal, so that the identification of causative genes has allowed prenatal diagnosis for many diseases giving a greater hope of survival thanks to a more adequate and prompt management.
Keywords: Airways diseases